ИСТОРИЧЕСКИЕ ЭТАПЫ РАЗВИТИЯ СОЦИАЛЬНО-ЭКОНОМИЧЕСКОЙ И ЭКОЛОГИЧЕСКОЙ ПОЛИТИКИ КАРАКАЛПАКСТАНА В ГОДЫ НЕЗАВИСИМОСТИ (1991-2021гг.) - Джумагельдиев, Н.Р. (SCIENCE and SOCIETY, 2024)
The article discusses issues of research into the historical stages of development of the analysis carried out on the development of stages of environmental policy, socio-economic and environmental policy of Karakalpakstan during the years of independence (1991-2021).
Keywords: Karakalpakstan; stages of development of environmental policy; socio-economic criteria; national strategy; sustainable development